2018
DOI: 10.1038/s41524-018-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly large energy variations from dopant interactions in ferroelectric HfO2 from high-throughput ab initio calculations

Abstract: Insight into the origin of process-related properties like small-scale inhomogeneities is key for material optimization. Here, we analyze DFT calculations of randomly doped HfO 2 structures with Si, La, and V O and relate them to the kind of production process. Total energies of the relevant ferroelectric Pbc2 1 phase are compared with the competing crystallographic phases under the influence of the arising local inhomogeneities in a coarse-grained approach. The interaction among dopants adds to the statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
(86 reference statements)
3
18
0
Order By: Relevance
“…The results, represented by open green symbols in Figure a, show that the PE‐t state becomes dominant as the amount of Si grows. (A similar stabilization of PE‐t has already been reported in the study by Falkowski et al) Even more interestingly, our results also show that the FE‐o polymorph becomes more stable than the PE‐m state for Si concentrations of 12.5–25%.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The results, represented by open green symbols in Figure a, show that the PE‐t state becomes dominant as the amount of Si grows. (A similar stabilization of PE‐t has already been reported in the study by Falkowski et al) Even more interestingly, our results also show that the FE‐o polymorph becomes more stable than the PE‐m state for Si concentrations of 12.5–25%.…”
supporting
confidence: 91%
“…In our simulations with representative tetravalent dopants, it quickly became clear that (some) doping atoms have a (very strong) preference to adopt specific spatial arrangements. An important conclusion follows: it is not appropriate to assume—as implicitly done in the all cited DFT works except the study by Falkowski et al and, to some extent, the study by Künneth et al—that the dopants locate randomly in the HfO2 lattice. We thus focus on this issue and address the following questions: What is the preferred spatial configuration of substitutional cation dopants in HfO2?…”
mentioning
confidence: 99%
“…They found the most significant stabilization of the ferroelectric phase for oxygen rich processing conditions like in atomic layer deposition (ALD) and a competition between ferroelectric and tetragonal phase for oxygen poor processing. A high‐throughput study by Falkowski et al confirmed the results with a much higher number of relaxed structures. While a reproduction of the remarkable P r of 40 µC cm –2 has never been reported in subsequent publications, a recent work by Schroeder et al achieved P r between 25 and 30 µC cm –2 for a wide dopant concentration range …”
Section: Introductionmentioning
confidence: 74%
“…A high-throughput study by Falkowski et al [9] confirmed the results with a much higher number of relaxed structures. They found the most significant stabilization of the ferroelectric phase for oxygen rich processing conditions like in atomic layer deposition (ALD) and a competition between ferroelectric and tetragonal phase for oxygen poor processing.…”
mentioning
confidence: 70%
“…Zhou 26 on the other hand investigated several electronically compensated defect structures, consistent with the previously shown simulation results. 21,24 Falkowski 58 has investigated the effect of the spatial distribution of La and Si dopants including and not including vacancies. He found a stronger local variation of energy than expected with the implication that spatial arrangements of dopants have an effect on phase stability, distinguishing ALD from CSD processes.…”
Section: Doped Hfomentioning
confidence: 99%